The end of sexual identity : why sex is too important to define who we are - Paris, Jenell Williams (Downers Grove, Ill. : IVP Books, 2011)
Sexual identity has become an idol in both the culture at large and in the Christian subculture. Anthropologist Jenell Williams Paris offers a Christian framework for sexual holiness that accounts for complex postmodern realities. The end of sexual identity moves beyond culture-war impasses to open up new space for conversations in diverse communities both inside and outside the church.
Introduction: A word about sex -- What is defined as real -- The trouble with heterosexuality -- The trouble with homosexuality -- The promise of sexual holiness -- Sexual desire is (not) a big deal -- Having sex is (not) a big deal -- Celibacy is (not) a big deal -- Epilogue: The end is near.
Includes bibliographical references (p. [149]-155) and indexes.
Keywords: Sex -- Religious aspects -- Christianity; Homosexuality -- Religious aspects -- Christianity; Identity (Psychology) -- Religious aspects -- Christianity